La producción televisiva y su aporte para los pueblos indígenas Saraguro del cantón Yantzaza, en la provincia de Zamora Chinchipe - Tandazo Cuenca, Norman Isaías (2016)
The work called, THE TELEVISION PRODUCTION AND ITS CONTRIBUTION FOR INDIGENOUS TOWNS SARAGURO FROM YANZATZA CANTON, IN THE PROVINCE OF ZAMORA CHINCHIPE, is based on the implementation of the Law of Communications, and the role of the media as a resource for influence the development of towns. Through the approach of the central problem we seek How to facilitate social inclusion of towns and nationalities of the Yantzaza canton through a television program? In a social context in which, on the one hand, proposes a new constitutional framework that guarantees a real inclusion of towns and nationalities and, moreover, social actors as such and medias, not specify an approach that allows them interact and achieve true convergence and, above all, a relationship of mutual interest yet. Our overall objective is determine how television production influence in the Indigenous towns and indigenous Nationalities Saraguro from Yantzaza Canton. This work has led to significant bibliographic resources that reflect the incidence of the media, in this case television and also, make a greater cultural programming, as a proposal to true inclusion of these towns. The methodology used in this study was: the scientific, deductive, synthetic and analytical method, while in the used techniques, the tab observation, survey and interview, also instruments for data colectan were used as camera photographic and observation sheets. In the survey made in the San Vicente de Caney we got the following data: What about people living in the sector? It leaves us as a result, there is in this community 59% female persons and 41% male persons. Another of the questions asked is whether or not have a TV at home, 100% of homes in San Vicente de Caney have a television at home. What program do you see often? One of the most widely accepted programs are soap operas, this indicates that a cultural program format with these characteristics should be considered. With these results we conclude that the promotion of cultural programs directly linked to the peoples living in this area is necessary, we must consider that exists a majority of female persons, which should be directed programming